Evaluation of Chemical and Nutrient Constituents of Cocoyam and Soybean Flours and Their Blends - Imafidon, Monday Idiaghe; Ukhun, Mark Ehijele; Unuigbe, Charles Akhadelor; Irabor, Emmanuel Enoguan Ighodaro (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2024)
Food nutrients such as carbohydrates, fats, proteins and vitamins are essential for growth and development of man. Cocoyam (Colocasia esculenta), is a common tropical root crop cultivated in many parts of the world for food formulations and consumption by man. This study was conducted to assess some aspects of the chemical constituents and nutritive chemistry of cocoyam and soya bean flours and their blends.The sun-dried samples were milled separately to size (sieve with 25µm aperture size) to obtain homogenous flours. Blends were obtained with various ratios according to the percentage of soybean/cocoyam flours (10% (10g: 90g), 20% (20:80), 30 %( 30:70), 40 %( 40:60), 50% (50:50). The proximate compositions (moisture, crude protein, crude fat, ash, crude fibre and nitrogen-free extract) were determined using standard methods. while mineral elements (Na and K) were determined by flame photometry and Mg, Ca, Fe, Zn and Cu by atomic absorption spectrophotometry (AAS). Results obtained were subjected to statistical analysis using Microsoft Excel for graphs, SPSS for correlation and regression studies. G-stat was used to calculate coefficient of variation. The ranges of values for the proximate composition (%) of the products were: Crude protein (4.95+1.03 – 43.29+0.46), ash (3.25+0.25 – 7.25+2.75), moisture (8.42+0.28-12.38+1.03), crude fibre (3.00+0.50 – 8.25+0.75) and nitrogen-free extract (10.60+ 7.34 - 76.02+1.83). Mineral elements(mg/kg): Fe (1.00+0.28 – 2.65+0.21), Zn (0.12+0.04 – 0.22+0.03), Cu (0.00+0.00 - 0.15+0.07), Na (0.35+0.05 – 2.40+0.14), Mg (3.45+0.43 – 12.88+0.55), Ca (4.80+0.42 -10.55+0.64), K (39.65+2.33 – 56.25+0.78) and phosphorus (206.10+ 0.05 – 326.34+4.30). Bleeding of cocoyam flour with soybean flour gave products that could be of greater nutritional value than either cocoyam or soybean flour used separately.